Formulation of Nanoparticles Against TB - A Review - Kataria, Mandeep; Sethi, Manisha; Kaur, Jagjit; Punia, Sandeep; Kumar, Kuldeep (Recent Patents on Inflammation & Allergy Drug Discovery, 2015)
Tuberculosis is a major public health concern. The present article reviews the current updates on the usage of nanoparticles against tuberculosis and recent patents that could develop into novel therapeutics available to the clinical armamentarium for the TB management. The drug delivery systems involving nanoparticles are suitable against chronic diseases such as tuberculosis. Polymers in many forms like liposomes, dendrimers, Nanoemulsions can be used as synthetic and natural carriers for first line and second line drugs employed for chemotherapy. Not only are the drugs sustainably released in organs and plasma, but also their dosages as well as adverse effects have been reduced, the drug interaction has increased and the drug resistant bacteria have been targeted. The hurdles in the development of anti-tuberculosis have made Nano medicines to act as a silver lining.
Keywords: nanoparticles